DETERMINAN KEMISKINAN DI SUMATERA UTARA: STUDI KASUS 33 KABUPATEN/KOTA PERIODE 2020-2022 - Laila Campaka Wangi; Syahda Azmi Syahidah; Estro Dariatno Sihaloho (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Indonesia has committed to support the Sustainable Development Goals (SDGs) launched by the United Nations (UN), one of which is the first SDG that aims to eliminate poverty in various forms. Although the government has made various efforts to reduce poverty, this problem is still one of the government's focuses that requires continuous handling. The phenomenon of poverty in Indonesia is also exacerbated by the low quality of labor which results in low productivity and ultimately has an impact on low wages. The purpose of this study is to determine the determinants that affect Poverty in 33 Cities/Regencies in North Sumatra in the period 2020 to 2022. This study uses panel data analysis, namely the Fixed Effect Model (FEM). The regression results show that the Open Unemployment Rate and Regency / City Minimum Wage have a positive and significant effect on poverty in 33 districts / cities in North Sumatra. Meanwhile, HDI has a negative and significant effect on poverty in 33 districts/cities in North Sumatra.